Strategi Manajemen Sistem Informasi Dalam Administrasi Kesiswaan Di SDN 03 Cot Girek - Ria Resti Sinaga; Rayyan Firdaus (Akuntansi, 2024)
, In the era of globalization, Information technology advancements have a big impact on a lot of different parts of life, including education. The integration of technology in learning systems and processes is crucial, especially in the context of educational institutions. The purpose of this study is to define and evaluate management information systems (SIM) strategies in student administration services at SDN 03 Cot Girek. This study employs a case study methodology, qualitative data collection methods, and data analysis strategies supported by Atlas.ti 8 software. The results of the research show that SDN 03 Cot Girek has succeeded in integrating information technology in administrative services to students. This is done by utilizing technology and internet networks and actively involving teachers. Implementation of this strategy produces quality educational services.It is expected that this research will be beneficial to SDN 03 Cot Girek and the surrounding community. By developing an effective and efficient management information system, SDN 03 Cot Girek can raise and enhance the standard of education public satisfaction with information about SDN 03 Cot Girek. This study can be used as a template for other academic establishments in developing effective and efficient management information systems.